Mesiodistal angulations of the mandibular canines, premolars and molars with or without the presence of third molars - Cuoghi, Osmar Aparecido [UNESP]; Sella, Rodrigo Castellazzi [UNESP]; Mendonça, Marcos Rogério de [UNESP] (Oxford University Press, 2010)
The results show that, in both groups, the mandibular premolars and molars had enhanced angulation in the mesial direction, when compared with a control group of 42 Caucasians ranging in age from 12 to 17 years with a 'normal' occlusion (P < 0.05), while the mesiodistal axial angulation of the mandibular canines was similar to the control group (P < 0.05). The two groups, when compared, exhibited similar angular values for the canines, premolars and mandibular molars (P < 0.05), indicating no influence of the third molars.